Promotion of conjunctival fibroblast-mediated collagen gel contraction by mast cells through up-regulation of matrix metalloproteinase release and activation. (May 2022) - Kishimoto, Tatsuma; Ishida, Waka; Nakajima, Isana; Taguchi, Osamu; Sugioka, Koji; Kusaka, Shunji; Fukuda, Ken
Abstract: Mast cells and conjunctival fibroblasts contribute to conjunctival wound healing and allergic ocular inflammation. The number of mast cells in the conjunctiva is increased in individuals with cicatricial fibrosis-causing ocular surface diseases and after glaucoma filtering surgery, suggesting that these cells may contribute to the scarring observed after such surgery. We studied the potential mechanism of fibroblast–mast cell interaction in the healing of conjunctival wounds using a three-dimensional collagen gel culture system. We found that mast cells derived from the bone marrow of mice embedded in a collagen gel did not induce gel contraction. However, an increase in mast cells was associated with increased collagen gel contraction mediated by mouse conjunctival fibroblasts. The extent of collagen degradation was not affected by the co-culture of mast cells and conjunctival fibroblasts. Gelatin zymography disclosed that mast cells increased the amounts of both the pro form of matrix metalloproteinase (MMP)–9 and the active form of MMP-2 in supernatants of conjunctival fibroblast cultures. Furthermore, the potentiating effect of mast cells on contraction of the collagen gel through conjunctival fibroblasts was attenuated by the addition of a synthetic MMP inhibitor. Thus, current results suggest that mast cells accelerate the conjunctival fibroblast-dependent contraction of collagen gel by increasing the release as well as activation of MMPs. Therefore, the interaction between mast cells and conjunctival fibroblasts may contribute to conjunctival scar formation after glaucoma filtering surgery. Highlights: Mast cells promote collagen gel contraction dependent on conjunctival fibroblasts. Mat cells increase the release and activation of MMPs by conjunctival fibroblasts. Interaction between fibroblasts and mast cells contribute to conjunctival scarring.